Morphological markers for the detection of introgression from cultivated into wild carrot (Daucus carota L.) reveal dominant domestication traits. (22nd November 2012) - Grebenstein, C.; Kos, S. P.; de Jong, T. J.; Tamis, W. L. M.; de Snoo, G. R.
Abstract Hybridisation and subsequent introgression have recently received much attention in the context of genetically modified crops. But crop–wild hybrid detection in the field can be difficult, as most domestication traits seem to be recessive, and the hybrid phenotype may also depend on the direction of the cross or environmental factors. Our aim was to develop a reliable set of morphological markers that differ between two wild and 13 cultivated carrots (Daucus carota L.) and to evaluate their inheritance in hybrid lines. We then examined these morphological markers in four F1 hybrids obtained by fertilising plants from the two wild accessions with pollen from two common carrot cultivars. Of the 16 traits that differed between the two carrot subspecies, three took intermediate values in the hybrids, eight resembled the cultivar parent (dominant domestication traits), two resembled the wild parent (domestication traits recessive), and three were not significant or growth condition‐dependent. Root:shoot ratio was seven times higher for cultivars than for wild plants, while still attaining equivalent total dry weight, which shows that dry matter production by the shoot is much higher in cultivars than in wild plants. High root:shoot ratios were also present in the hybrids. While we found no maternal effects, the type of cultivar used for pollination had an impact on hybrid characteristics. The morphological markers developed here provide insights into the mode of inheritance of ecologically relevant traits and can be useful for pre‐screening wild populations for hybrid detection prior to genetic analysis.